IND-2, a Quinoline Derivative, Inhibits the Proliferation of Prostate Cancer Cells by Inducing Oxidative Stress, Apoptosis and Inhibiting Topoisomerase II - Swapnaa Balaji; Rabin Neupane; Saloni Malla; Rahul Khupse; Haneen Amawi; Shikha Kumari; Diwakar Bastihalli Tukaramrao; Srestha Chattopadhyay; Charles R. Ashby; Sai H. S. Boddu; Chandrabose Karthikeyan; Piyush Trivedi; et al. (Life, 2022)
In men, prostate cancer (PC) is the most frequently diagnosed cancer, causing an estimated 375,000 deaths globally. Currently, existing therapies for the treatment of PC, notably metastatic cases, have limited efficacy due to drug resistance and problematic adverse effects. Therefore, it is imperative to discover and develop novel drugs for treating PC that are efficacious and do not produce intolerable adverse or toxic effects. Condensed quinolines are naturally occurring anticancer compounds. In this study, we determined the in vitro efficacy of IND-2 (4-chloro-2-methylpyrimido[1″,2″:1,5]pyrazolo[3,4-b]quinolone) in the PC lines, PC-3 and DU-145. IND-2 significantly inhibited the proliferation of PC-3 and DU-145, with IC50 values of 3 µM and 3.5 µM, respectively. The incubation of PC-3 cells with 5 and 10 µM of IND-2 caused the loss of the mitochondrial membrane potential in PC-3 cells. Furthermore, IND-2, at 5 µM, increased the expression of cleaved caspase-3, cleaved caspase-7 and cleaved poly (ADP-ribose) polymerase (PARP). The incubation of PC-3 cells with 5 µM of IND-2 significantly decreased the expression of the apoptotic protein, B-cell lymphoma 2 (Bcl-2). Furthermore, 5 and 10 µM of IND-2 produced morphological changes in PC-3 cells characteristic of apoptosis. Interestingly, IND-2 (2.5, 5 and 10 µM) also induced mitotic catastrophe in PC-3 cells, characterized by the accumulation of multinuclei. The incubation of DU-145 cells with 1.25 and 5 μM of IND-2 significantly increased the levels of reactive oxygen species (ROS). Finally, IND-2, at 10 μM, inhibited the catalytic activity of topoisomerase IIα. Overall, our findings suggest that IND-2 could be a potential lead compound for the development of more efficacious compounds for the treatment of PC.